Studies in Conservation:A Bibliometric Survey - Senapati, S. K. (Journal of Information and Knowledge, 1995)
Analyses numerically the year and language wise distribution and break up of papers published in ’Studies in conservation’ for five years from 1988 to 1992 in respect of country and type of organisation to which author belongs, authorship pattern, subject areas, references, average number of illustration.